2015
DOI: 10.12998/wjcc.v3.i2.180
|View full text |Cite
|
Sign up to set email alerts
|

Use of steroids for facial nerve paralysis after parotidectomy: A systematic review

Abstract: Corticosteroids do not appear to improve FNP prognosis post-parotidectomy. Further studies assessing patients by cohort and with long term follow-up are required to increase scientific evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…20 Conversely, numerous studies showed corticosteroids to be ineffective in preventing neuronal injury or in hastening recovery among patients undergoing parotidectomy. 21-23…”
Section: Discussionmentioning
confidence: 99%
“…20 Conversely, numerous studies showed corticosteroids to be ineffective in preventing neuronal injury or in hastening recovery among patients undergoing parotidectomy. 21-23…”
Section: Discussionmentioning
confidence: 99%
“…It was found out that in cases after surgical interventions on the parotid and submandibular glands, during which there is an extension of the branches of the facial nerve during the operation, the neuropathy of the nerve can be observed in the postoperative period [10][11][12][13][14][15][16][17]. The fact of the existence of the neuropathy of the facial nerve, caused by its stretching, is proved in patients after surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of perioperative corticosteroids on facial nerve outcomes following parotid surgery is based on a systematic review of randomized controlled trials (level 1 evidence), two randomized controlled trials (level 1 evidence), one retrospective cohort study (level 3 evidence), and one preclinical investigation (level of evidence: not applicable).…”
Section: Level Of Evidencementioning
confidence: 99%
“…Facial nerve paralysis (FNP) is a potential complication following parotid surgery. Despite meticulous dissection, identification of key landmarks, and gross preservation of neural tissue, the incidence of transient FNP following parotidectomy varies from 12% to 40% . Although independent tumor and patient risk factors (tumor size, pathology, recurrent disease, deep lobe location, nerve involvement, revision surgery, radiation therapy) may alter prognosis, attempts to improve facial nerve outcomes are based on literature supporting anti‐inflammatory modalities such as corticosteroids.…”
Section: Introductionmentioning
confidence: 99%